Synthesis, characterization, thermal, and antibacterial activity studies on MgO powders - GÜLLÜOĞLU, ARİF NİHAT; KIRAN YILDIRIM, BERÇEM; TÜNÇAY, MEHMET MASUM; DEMİRCİ, SELİM (SPRINGER, 2021)
In this study, MgO particles were synthesized via sol-gel technique and calcined at 600 degrees C for 2 h with heating rates of 2, 5, 10, and 20 degrees C/min, respectively, for the first time. Comprehensive characterizations were performed by TGA-DTA, XRD, SEM, Raman spectroscopy, BET analysis, photoluminescence techniques. The kinetic parameters were determined by employing four popular model-free methods: Flynn-Wall-Ozawa (FWO), Kissinger-Akahira-Sonuse (KAS), Starink, and Tang methods. MgO powders had a high crystalline structure regardless of different heating rates based on XRD results. Surface morphologies and surface areas of MgO powders did not change with heating rates. Surface morphologies of MgO powders were found to be nearly spherical with some rounded shape and exhibiting faceted edges in some regions. The specific surface area of MgO powders was found to be 5.9179, 5.6883, 3.6617, and 4.1942 m(2)/g with increasing heating rate, respectively. According to Raman analysis, MgO particles produced at 2 degrees C/min possessed higher surface defects like oxygen vacancies. The PL emission signals for MgO particles were observed at similar to 500 nm consisting of broad peaks, which might be attributed to oxygen defects on the surface of particles. The antibacterial performances of MgO particles were carried out against gram-negative E. coli and gram-positive B. subtilis by means of the agar disc diffusion method. MgO particles produced at a heating rate of 2 degrees C/min possessed the biggest inhibition zone against gram-positive B. subtilis. Having better antibacterial performances for MgO particles produced at 2 degrees C/min heating rate might be attributed to surface oxygen vacancies and surface area, which led to the generation of more reactive oxygen species (ROS). [GRAPHICS] .
Keywords: MgO particles; Sol-gel method; Antibacterial activity; Thermodynamic properties; Heating rate; OXIDE NANOPARTICLES; ACTIVATION-ENERGY; GEL; TOXICITY; KINETICS